Cost of cataract surgery after implantation of three intraocular lenses - Catherine Boureau (Dove Medical Press, 2009)
Catherine Boureau1, Antoine Lafuma2, Viviane Jeanbat2, Andrew F Smith3, Gilles Berdeaux41Clinique Geoffroy St Hilaire, Paris, France; 2Cemka-Eval, Bourg la Reine, France; 3Alcon Laboratories Ltd, Hemel Hempstead, UK and Nuffield Laboratory of Ophthalmology, University of Oxford, UK; 4Alcon France, Rueil Malmaison, France; Conservatoire National des Arts et Métiers, Paris, FranceBackground: Posterior capsule opacification is one of the most frequent adverse events following cataract surgery. This manuscript reports the lifetime cost of complications linked to posterior capsule opacification using three types of intraocular lens with square edges.Methods: Costs were estimated from a retrospective study of patients who underwent cataract surgery and data from the literature. The lenses studied were hydrophobic acrylic (SA60AT and AR40E) and hydrophilic acrylic (XL-Stabi) lenses with square edges. The frequency of Nd-Yag laser capsulotomies after 4 years’ survival was estimated by two methods: the first involved linear adjustment of the rate at 5 and 6 years follow-up and then application of a constant rate after 6 years; the second involved linear adjustment after 5 years follow-up. The economic perspective was that of the French Sickness Fund.Results: After 3 years’ follow-up the percentage of patients who had not undergone laser Nd-Yag capsulotomy was 86.9% with SA60AT, 76.6% with AR40E and 54.6% with XL-Stabi lenses (p < 0.001). The total cost of capsulotomy and management of complications per patient lifetime was estimated to be €90.5 for SA60AT, €189.5 for AR40E and €288.0 for XL-Stabi lenses by the first extrapolation method. With the second method of extrapolation the costs were €94.8, €200.0 and €300.2, respectively.Interpretation: Lower costs for cataract surgery and management of related complications were observed with the two hydrophobic acrylic lenses; the lowest costs were observed with SA60AT lenses as they were associated with fewer Nd-Yag laser capsulotomies.Keywords: cataract surgery, Nd-Yag laser, capsulotomy, adverse event, cost, budget impact